Galvanic Corrosion of Copper / Nickel-Chrome Alloy in an Agitated Sulfuric Acid Solution - Hussein, Samar S.; Hasan, Basim O.; Al-Haboubi, Naseer A. (Al-Nahrain Journal for Engineering Sciences, 2018)
Galvanic corrosion of Nickel-Chrome alloy (Ni-Cr alloy) and Copper (Cu) coupled in 5% sulfuric acid solution was investigated. The effects of agitation velocity, temperature, and time on the galvanic corrosion current and the weight loss of both metals in both free corrosion and galvanic corrosion were investigated. The trends of open circuit potential (OCP) of each metal and galvanic potential (Eg) of the couple were also determined. The results showed that Cu was cathodic relative to Ni-Cr alloy in galvanic couple and the corrosion potential of the couple (Ni- Cr alloy /Cu) was between the values of the two single components because the OCP of copper shifted to positive with the increase in velocity. Under stagnant conditions initially the galvanic current was more negative then shifted to the positive with time. The corrosion of Ni-Cr alloy decreased with time because the passivation layer was formed on the surface. Under flow conditions, the galvanic current sharply shifted to the negative direction (increase galvanic current from Ni-Cr alloy (anode) to Cu (cathode) during the first few minutes.